A new species and new records of the genus Hypogastrura Bourlet, 1839 (Collembola, Hypogastruridae) from Iran - Kahrarian, Morteza; Vafaei-Shoushtari, Reza; Skarżyński, Dariusz; Konikiewicz, Marta; Soleymannezhadyan, Ebrahim; Mehr, Masoumeh Shayan; Shams, Bahman (Zootaxa, 2013)
Hypogastrura persica sp. nov. is described from the Zagros Mountains (Kermanshah Province, Iran). The new species can be distinguished from two nearest congeners, namely H. exigua Gisin, 1958 (Alps) and H. magistri Babenko, 1994 (Siberia), by the body size, the number of sensilla on antennal segment IV, the number of setae on dens and ventral tube as well as chaetotaxy of abdominal terga IV and V. Three species of the genus, viz. H. martiani Skarżyński & Kaprus’, 2009, H. purpurescens (Lubbock, 1867) and H. socialis (Uzel, 1891), have been recorded from Iran for the first time.